Lithium in the aragonite skeletons of massive Porites corals: A new tool to reconstruct tropical sea surface temperatures. (25th March 2013) - Hathorne, Ed C.; Felis, Thomas; Suzuki, Atsushi; Kawahata, Hodaka; Cabioch, Guy
Abstract : [1] Previous studies have demonstrated the potential for the Li content of coral aragonite to record information about environmental conditions, but no detailed study of tropical corals exists. Here we present the Li and Mg to Ca ratios at a bimonthly to monthly resolution over 25 years in two modern Porites corals, the genus most often used for paleoclimate reconstructions in the tropical Indo‐Pacific. A strong relationship exists between coral Li/Ca and locally measured SST, indicating that coral Li/Ca can be used to reconstruct tropical SST variations. However, Li/Ca ratios of the skeleton deposited during 1979–1980 do not track local SST well and are anomalously high in places. The Mg/Ca ratios of this interval are also anomalously high, and we suggest Li/Ca can be used to reconstruct tropical SST only when Mg/Ca data are used to carefully screen for relatively rare biological effects. Mg/Li or Li/Mg ratios provide little advantage over Li/Ca ratios, except that the slope of the Li/Mg temperature relationship is more similar between the two corals. The Mg/Li temperature relationship for the coral that experienced a large temperature range is similar to that found for cold water corals and aragonitic benthic foraminifera in previous studies. The comparison with data from other biogenic aragonites suggests the relationship between Li/Mg and water temperature can be described by a single exponential relationship. Despite this hint at an overarching control, it is clear that biological processes strongly influence coral Li/Ca, and more calibration work is required before widely applying the proxy. Key Points: Strong relationship between coral Li/Ca ratios and locally measured SST found Li/Ca faithfully records SST when Mg/Ca ratios are anti‐correlated with Li/Ca Li and Mg incorporation into corals is strongly affected by biological processes